Perancangan Dashboard Persiapan Cabang untuk Go-Live ERP pada PT. X - Clairine Susilo; Siana Halim (Jurnal Titra, 2023)
PT.X is a company engaged in gas manufacturing, which is carrying out an ERP system replacement project. This study discusses the design of branch readiness dashboards in the process of replacing ERP PT.X based on branch performance calculations. Branch performance displayed on the dashboard is calculated through several categories of activities that are often carried out by each branch, namely, scan filling, scan delivery, verification, delivery without barcodes, customer audits, and on-truck bottle balances. The dashboard consists of 1 page which is divided into 7 main tables where the 6 tables display detailed performance score figures for all PT.X branches for each category. Meanwhile, the last table displays the final calculation of the performance score for all branches. The branch readiness dashboard is designed to measure the performance of a branch whether it is ready or not in carrying out the ERP transformation process.